Interferon regulatory factor 5: a potential target for therapeutic intervention in inflammatory diseases - Yu, Xinyuan; Rehman, Ata Ur; Dang, Lihong; Zhang, Xu; Liu, Jia; Xiong, Xiaoxing; Chen, Gang; Jian, Zhihong (Frontiers in Immunology, 2025)
Interferon regulatory factor 5 (IRF5) is a critical transcription factor in the IRF family, playing a pivotal role in modulating immune responses, particularly within the innate immune system. IRF5 regulates the expression of type I interferons (IFNs), proinflammatory cytokines, and other immune-related genes, essential for effective host defense against infections and immune surveillance. Its functions, however, are diverse and highly context-dependent, adapting to different immune challenges and tissue environments. Studies have demonstrated that dysregulated IRF5 activation contributes to the pathogenesis of numerous diseases, including cancer, autoimmune disorders, and chronic inflammatory conditions such as systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA). This dysregulation underscores the dual role of IRF5, both in immune protection and in driving pathological inflammation. Given its significant involvement in both physiological and pathological processes, IRF5 presents a promising therapeutic target for managing diseases characterized by excessive inflammation and immune dysregulation. However, developing effective molecules to specifically modulate the IRF5 pathway remains challenging, with limited therapeutic agents available for clinical application. In this review, we examine the diverse roles of IRF5 in various disease contexts, the mechanisms by which IRF5 contributes to disease progression, and the potential therapeutic strategies targeting IRF5. Additionally, we discuss potential complications and risks associated with IRF5-targeted therapies, including the balance between dampening pathological inflammation and preserving essential immune functions. This exploration highlights both the therapeutic potential and the complexity of modulating IRF5 activity in clinical settings.